2016
DOI: 10.1038/mtna.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

The Novel miR-9600 Suppresses Tumor Progression and Promotes Paclitaxel Sensitivity in Non–small-cell Lung Cancer Through Altering STAT3 Expression

Abstract: MicroRNAs have been identified to be involved in center stage of cancer biology. They accommodate cell proliferation and migration by negatively regulate gene expression either by hampering the translation of targeted mRNAs or by promoting their degradation. We characterized and identified the novel miR-9600 and its target in human non–small-cell lung cancer (NSCLC). Our results demonstrated that the miR-9600 were downregulated in NSCLC tissues and cells. It is confirmed that signal transducer and activator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…17,18 In this regard, several miRNAs have been reported to suppress or promote lung cancer cell survival or death. [19][20][21][22] Consistent with these reports, we have previously reported that miR-886-3Pwas associated with survival of SCL. 23 In the current study, we further investigated role of miR-886-3P in regulating small cell lung caner cell proliferation, migration, colony formation, mesenchymal-epithelial transition (MET), and in vivo xenograft tumor formation and growth.…”
Section: Introductionsupporting
confidence: 87%
“…17,18 In this regard, several miRNAs have been reported to suppress or promote lung cancer cell survival or death. [19][20][21][22] Consistent with these reports, we have previously reported that miR-886-3Pwas associated with survival of SCL. 23 In the current study, we further investigated role of miR-886-3P in regulating small cell lung caner cell proliferation, migration, colony formation, mesenchymal-epithelial transition (MET), and in vivo xenograft tumor formation and growth.…”
Section: Introductionsupporting
confidence: 87%
“…Accumulating literatures have documented that miR-7, as a promising tumor suppressor, could regulate the biological behavior of human lung cancer cells 1, 12, 13. Moreover, our previous research works also showed that overexpression of miR-7 could inhibit the growth of human lung cancer cells 17, 18.…”
Section: Resultsmentioning
confidence: 81%
“…The overall 5-year survival rates for surgical resection in lung cancer patients still remain poor. Thus, it is important to identify and characterize new molecular markers and genes to develop more targeted treatment strategies to improve the clinical outcome of lung cancer 1, 2, 3. Recent evidence showed that the technique of targeted gene expression, including specific gene-promoter-operating expression and distinct delivery systems, is a crucial strategy for gene therapy against various cancers including lung cancer 4, 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…For transient transfection assays, cells were transfected with plasmids of JNK1 expression or siRNAs of JNK1 and Brf1 as described previously (Fang et al ., 2016; Sun et al , 2016BC). Serum-free medium was added to each dish with Lipofectin-DNA or Lipofectamine 2000-siRNA complexes, and cells were further incubated for 4h.…”
Section: Methodsmentioning
confidence: 99%